Relationships between yo-yo intermittent recovery tests and development of aerobic and anaerobic fitness in U-13 and U-17 soccer players - Chuman, K.; Hoshikawa, Y.; Iida, T.; Nishijima, T. (International Journal of Sport & Health Science, 2011)
The study investigated the Yo-Yo intermittent recovery level 1 and level 2 tests (YYIR1 and YYIR2) performed by soccer players at puberty (U-13) and post-puberty (U-17) and related the YYIR1 and YYIR2 results to anaerobic and aerobic fitness. The subjects were sixteen male pubescent players aged 13.3(0.2) yrs (U-13) and fifteen male post-pubescent players aged 17.0(0.6) yrs (U-17). The subjects performed YYIR1 and YYIR2 on artificial turf and were also measured for fat-free mass (FFM), Wingate anaerobic test and VO2max during treadmill running in a laboratory. The results in YYIR1 and YYIR2 (2365 and 843 m) for the U-17 were significantly higher than the U-13 (1963 and 550 m). Results from YYIR1 and YYIR2 in the U-17 correlated significantly with VO2max (r=0.76 and 0.53) but not with Wingate anaerobic test, whereas YYIR1 and YYIR2 results in the U-13 correlated significantly with Wingate anaerobic test (r=0.61 and 0.64) but not with VO2max even though they showed high VO2max levels. The correlation coefficient of VO2max with YYIR1 and YYIR2 in the U-17 was equivalent to those reported in adult players and indicated that VO2max determined YYIR1 and YYIR2 performances moderately and highly in post-pubescent players. However, neither of the YYIR1 and YYIR2 performances in the U-13 reflected aerobic fitness but did reflect anaerobic fitness.